Analisis Figur Minat Wisatawan Mengenai Tren Wisata Coolcations - Ety Setiawati; Dian Fitriyana (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Coolcations tourism is an alternative tourism that utilizes the potential of nature with cool air, both in the morning, afternoon, and evening, thus providing a refreshing holiday experience for tourists. This concept combines recreational activities with the beauty and coolness of nature, making it suitable for tourists who want to escape the hustle and bustle of urban life. Based on the author's observations, Kuningan Regency has great potential in developing coolcations destinations, which include various activities such as camping/glamping, sightseeing, forest bathing, wellness tourism, star bathing, night time wellness, hiking, trekking, jeep adventure, motocross, and cycling. This study aims to determine the figure of tourist interest, especially those from Cirebon City and Regency, towards the trend of coolcations tourism in Kuningan Regency. The research method used is descriptive quantitative with a purposive sampling technique. The research sample amounted to 100 respondents who were tourists from Cirebon City/Regency. The research instrument used an online questionnaire via Google Form. Data were analyzed using univariate analysis techniques with the application of the Guttman Scale to measure the level of respondent interest. The research results indicate that tourist interest in the coolcation trend in Kuningan Regency is high. The average "YES" response was 84.75 out of 100, which, when converted to a percentage, is 84.75%. Based on the assessment criteria, this result falls into the "good interest" category with a high criterion (75%–100%). This finding indicates that tourists from Cirebon City/Regency have significant interest in coolcation tourism activities in Kuningan Regency. With its supportive natural resources and high interest, Kuningan Regency has a significant opportunity to develop coolcations as a leading regional tourism attraction.